Avenues for biofortification of zinc in barley for human and animal health: a meta-analysis - Khan, Waleed Amjad; Shabala, Sergey; Cuin, Tracey Ann; Zhou, Meixue; Penrose, Beth (Plant and soil, 2021)
Background and aims Zinc (Zn) deficiency in humans is of worldwide concern and is primarily associated with a plant-based diet of crops grown in Zn-deficient soils. This work explores the effects of both soil factors and genotype on Zn accumulation in aboveground tissues in barley ( Hordeum vulgare L.). Methods A meta-analysis was performed on collected articles data published between 1945-2020 describing Zn concentrations in barley shoots and grains in plants grown at different levels of Zn availability. Results Higher Zn levels in the growth substrate resulted in increased Zn concentrations in barley shoots and grains. Of note is that Zn concentrations were found to be highly cultivar specific, with a 3.5-fold (shoots) to 4.5-fold (grains) difference reported between high and low Zn accumulating cultivars under the same conditions. Additionally, the Zn translocation and remobilisation rate from shoots to grains were also 2-fold greater in Zn-efficient cultivars than others. Conclusions This meta-analysis is the first to collect all available data regarding Zn concentrations in barley. The findings demonstrate that Zn concentrations in aboveground parts of barley are highly cultivar-specific and change with substrate Zn. Target Zn concentrations in barley could be achieved through selective breeding and optimal Zn fertilisation. Further investigations revealing the major quantitative trait locus (QTLs) and candidate genes associated with desirable Zn phenotypes would allow better understanding of Zn use mechanisms in barley.